Towards an understanding of the organizational sustainability in youth association - Mohd Fauzi, Noor Khalifah; Arshad, Mohd Mursyid; Krauss, Steven Eric (Faculty of Educational Studies, Universiti Putra Malaysia, 2018)
This paper aims for the understanding of organizational sustainability where it focuses on the youth association especially in Selangor. This paper also will review on the definition of organizational sustainability to see how it relates to the context of youth association. In this era, the organization built has changed with the revolution of the new trends like climate change, globalization, demographic change and diversity has become the critical challenge to the traditional organizational style with its spotlight on shareholder value. This study aims to explore further about organizational sustainability from the continuity of previous related studies. All of the changes in Malaysia including policy and regulations has inspired for the youth as the change agent for development in Malaysia. Based on the traits theory and triple bottom line model of sustainability, there are three elements including financial, social and environment of sustainability. This study is a conceptual paper that explains about the organizational sustainability in non-profit organization which referred to youth association.